2017
DOI: 10.1002/chem.201605610
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective α‐Cyanation with 4‐Acetylphenyl Cyanate

Abstract: A highly effective asymmetric version of α-cyanation of β-keto esters and amides was developed with a Lewis-acid catalyst. Thus, by using 10 mol % of a tridentate bisoxazoline-zinc(II) complex as the catalyst, a series of chiral nitriles containing a quaternary carbon center were obtained in excellent enantioselectivities (up to 97 % enantiomeric excess) and up to 95 % yield in the presence of 4 Å molar sieve at room temperature. For the first time, mild and active 4-acetylphenyl cyanate was used instead of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…To explain the stereochemical outcome of the reaction, the authors proposed the catalytic cycle depicted in Scheme 83. After formation of the initial dinuclear zinc catalyst, Scheme 84. a-Cyanations of b-ketoesters and b-ketoamides with p-acetylphenylcyanate in the presence of a bisoxazoline ligand [119].…”
Section: Hydrosilylations Of Carbonyl Compounds and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain the stereochemical outcome of the reaction, the authors proposed the catalytic cycle depicted in Scheme 83. After formation of the initial dinuclear zinc catalyst, Scheme 84. a-Cyanations of b-ketoesters and b-ketoamides with p-acetylphenylcyanate in the presence of a bisoxazoline ligand [119].…”
Section: Hydrosilylations Of Carbonyl Compounds and Derivativesmentioning
confidence: 99%
“…Along with a-aminations, asymmetric a-cyanations of bketocarbonyl compounds have been developed in the presence of chiral zinc catalysts. For example, Chen et al reported a novel methodology for enantioselective a-cyanation of b-ketoesters which was based for the first time on the use of p-acetylphenyl cyanate 247 as cationic cyano source [119]. As illustrated in Scheme 84, the reaction of the latter with a series of b-ketoesters 248 performed at room temperature in dichloromethane as solvent in the presence of a chiral zinc catalyst in situ generated from 10 mol% of Zn(BF 4 ) 2 (H 2 O) 6 and 12 mol% of bisoxazoline ligand (S, S)-249 yielded the corresponding chiral a-nitriles 250 in both moderate to high yields (30-95%) and enantioselectivities (47-97% ee).…”
Section: Other A-functionalizationsmentioning
confidence: 99%
“…As shown in Scheme 24, the bisoxazoline-based zinc complex prepared from Zn(II) salts with the tridentate dibenzofuran bisoxazoline 12 was found to be effective for the enantioselective cyanation of β-keto esters and amides with readily available 4-acetylphenyl cyanate, which has good solubility and mild reactivity. 42 The presence of an acetyl group at the 4-position of the cyanate is essential for achieving a high degree of enantioselectivity. When 10-20 mol% of the catalysts in CH 2 Cl 2 are used in the reaction at room temperature, both five-and six-membered esters and amides were converted into the corresponding products in excellent yields and with up to 97% ee, while the cyanation of a seven-membered ester resulted in a low enantioselectivity.…”
Section: Scheme 23 Asymmetric Electrophilic Cyanation Of β-Keto Carbomentioning
confidence: 99%
“…Flexible tridentate bisoxazoline ligand L3 resulted in slightly higher enantioselectivity (47%, entry 3). The combination of Cu­(OTf) 2 with dbfox ligands ( L4 – L7 , dbfox = 4,6-dibenzofurandiyl-2,2′-bisoxazoline) was found to provide very promising results (entries 4–7), and Cu­(OTf) 2 / L4 enabled the preparation of 3a in 86% yield with 66% ee (entry 4).…”
mentioning
confidence: 99%